Ana Maria Machado em sala de aula: leitura literária e formação do leitor - VIANA, Maria Helena da Silva (Universidade Federal do Pará, 2017)
This paper aims to present a methodological proposal to the reading of two works (Quem perde ganha e O Cavaleiro do Sonho: As aventuras e desventuras de Dom Quixote de La Mancha) by Brazilian writer Ana Maria Machado, intended for children and youth in order to encourage the literary literacy and the reader formation in a public school in the city of Ananindeua, in the state of Pará. It is considered, thus, the literary literacy as a right of all (Queirós, 2014) and the literary text being the core of the Portuguese discipline for being a manifestation of excellence of memory, of operation and creativity of Portuguese language (Silva, 1988). The literature teaching in public schools is target of criticism and has contributed timidly to form proficient readers, since the schooling process has occurred inappropriately and the teacher‟s challenge is to find the balance between the interests of personal enjoyment and the needs of literary schooling (Cosson, 2014). It is necessary, therefore, to rethink the problem so that the literacy text is not just nomenclatures object, grammatical banalities and superficial analysis (Smith, 2011), but an instrument that can raise reflections and relevant contribution to the lives of students. This paper is organized in three chapters: the first discusses the teaching of literature and the reader formation, the second deals with the literary universe of Ana Maria Machado and the third brings a proposal of pedagogic intervention. It is intended, this way, that the school promotes the insertion of children and youth literature and of the classical in their daily lives in order to contribute so that the reading of literary text be a meaningful and pleasurable activity for elementary school students and, thus, encourage the reader formation in public schools.